Women Participation in PRIs: Myth or Reality?? – A Study of Himachal Pradesh: Examining Women's Participation in PRIs in Himachal Pradesh (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In a country with a population of 1.3 billion and a sex ratio of 930 females to a 1000 males (48.20 females out of the total population ), keeping in mind the population trend it becomes really important to make sure that women has an equal part to play in every developmental aspect .The contribution of women counterpart cannot be ignored at any level of developmental process . The PRIs has provided women with an opportunity to contribute to the developmental process from the very basic level of development that is , the grassroots level of governance .With 33 reservation accorded to the women by the 73rd constitutional amendment act , the women became an integral part of local governance . The study focuses on the trends of women participation in PRIs in the State of Himachal Pradesh and the problems associated with women participation in PRIs.